Study of the Impact of the Hormonal Therapy and its Two Procedures (the Surgical and Medical Castration) in terms of PSA Values for Patients with Metastatic Prostate Cancer - كنعان محمد; نداف لؤي; زيبار سيامند (Latakia University Journal -Medical Sciences Series, 2020)
Background: The purpose of this study is to examine the outcomes of patients with metastatic prostate carcinoma who underwent medical or surgical castration. Materials and methods: The study began from March 2019 to March 2020 at Tishreen University Hospital, Lattakia, Syria and was conducted on 46 cases of metastatic prostate carcinoma divided into two groups, the first group 25 patients had surgical castration and the second one 21 patients had Medical castration .The PSA values were analysed in the first, third, and sixth month after treatment. Results: Mean follow up average was 6-9 months. In the initial 12 months, there were no statistical differences in the PSA normalization rate (P value=0.5147) but the real statistical difference was in how fast was the decrease in PSA values whereas P value =0.0475 after one month of treatment and then becomes P value =0.1814 after three month of treatment. Conclusion: Study shows no difference between the results of surgical and medical castration in terms of PSA values reduction, with superiority of surgical castration in terms of speed of PSA values decrease and quicker improvement of symptoms.